PENGARUH SRUKTUR KEPEMILIKAN, DEWAN KOMISARIS, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE - Afifah Mutaqiah, - (2019)
This study aims to determine the effect of Ownership Structure, Board of Commissioners, and Audit Committee of Tax Avoidance. This research uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 20152017.The sampling technique uses a purposive sampling method. Sample selection with a total of 50 manufacturing companies. The testing of the hypothesis used is the Data Panel Regression Analysis with program Eviews 9 and a significant level of influence of 5% (0.05). The results of this test show that (1) There is a significant influence of Ownership Structure, which is measured by the total proportion of institutional share ownership divided by the number of outstanding shares against Tax Avoidance with a significant level of 0.0016 smaller than the specified level a = 0.05, ( 2) There is a significant influence between the Board of Commissioners measured by the proportion of the number of independent commissioners divided by the total board against the Tax Avoidance with a significance level of 0.0004 smaller than the specified level a = 0.05, (3) There is a significant influence between the Audit Committee which is measured by the number of audit committees outside the company divided by the total audit committee against Tax Avoidance with a significance level of 0.0097smaller than the specified level a = 0.05.